Polymersomes-based curcumin delivery as cancer therapeutics - Castro, Karine C. [UNESP]; Barbosa, Leandro R.S.; Greaves, Tamar L.; Lopes, André M. (Elsevier, 2024)
Curcumin (CUR) is a phenolic molecule with yellow color and high bioactive capacity present in certain herbs and in particular found in turmeric rhizomes (including Curcuma longa Linn.). In addition to being used as a spice in several cultures, CUR has already established itself in the pharmaceutical field with several beneficial properties, such as antioxidant, antiinflammatory, and antimicrobial. Interestingly, CUR has immense antitumor activity, but its efficiency is limited due to some properties (e.g., low solubility, chemical instability, and reduced in vivo absorption rate). Nanostructures have been employed to surpass these challenges. In this way, polymersomes (PSs), which are nanostructures formed by self-assembling, are able to encapsulate hydrophilic and hydrophobic drugs simultaneously (or individually). PSs also have good encapsulation rates, robustness, and stealth capability, which result in low immunogenicity. This chapter overviews the literature on the encapsulation of CUR into PSs, focusing on its employment and effectiveness in cancer therapy.
Keywords: amphiphilic block copolymers (ABC); cancer therapy; chemotherapeutic agent; curcumin (CUR); nanostructures; Polymersomes (PSs); self-assembly; tumor cells